Evaluating the potential of culms from sugarcane and energy cane varieties grown in Argentina for second‑generation ethanol production - Ousmane Kane, Aissata (2021)
The efficient transformation of lignocellulosic biomass into fermentable sugars is essential for building bioeconomies. Sugarcane is an important agricultural crop in a number of Latin American countries, including Brazil and Argentina. Herein culms from two different sugarcane (SC384 and SC724) and two energy cane varieties (EC3116 and EC3118) bred in Argentina were evaluated for sustainable production of second-generation biofuels and green chemicals. Changes in the biomass crystallinity, structure, and morphology introduced by pretreatments were investigated using X-ray diffraction (DRX), confocal laser scanning microscopy (CLSM), and scanning electron microscopy (SEM) techniques. Enzymatic hydrolysis yields of untreated and pretreated sugarcane and energy cane culms were determined and correlated with physical analyses and chemical composition characterizations. Overall, after combined acid and alkali pretreatment, enzymatic convertibility was highly efficient for all studied sugarcane and energy cane varieties, reaching over 97% of theoretical conversion yields. High crystallinity indices and crystallite sizes of pretreated culms and SEM results and CLSM were consistent with the removal of lignin, solubilization of hemicellulose, and amorphous parts of lignocellulose imprinted by the pretreatments. High potential of culms from sugarcane and energy cane varieties cultivated in Argentina for sustainable production of renewable lignocellulosic sugars and their transformation into green chemicals and fuels was demonstrated.